A design science approach to developing an integrated mobile app forensic framework. Issue 105 (June 2021) - Zhang, Xiaolu; Liu, Charles Zhechao; Choo, Kim-Kwang Raymond; Alvarado, Jesus A.
Abstract: As our society becomes increasingly interconnected and reliant on technologies, the need for digital forensics is no longer restricted to cybercriminal investigations. For example, when a private organization's system is compromised due to unauthorized access or espionage, digital forensic investigations can help to reveal the 'what, why, how, who, when, and where' relating to the incident, and the findings can inform decision-making and mitigation strategy formulation. Taking an interdisciplinary lens, this paper uses the design science approach to guide the development of an integrated digital forensic framework. It is then demonstrated how the framework can be used by a forensic investigator to examine Android applications, using a series of case studies (also referred to as "instantiations" of the method artifact in the design science literature).